2007
DOI: 10.1039/b704509c
|View full text |Cite
|
Sign up to set email alerts
|

A potent bicyclic inhibitor of a family 27 α-galactosidase

Abstract: Two isomeric bicyclo[4.1.0]heptane analogues of the glycosidase inhibitor galacto-validamine, (1R*,2S,3S,4S,5S,6S*)-5-amino-1-(hydroxymethyl)bicyclo[4.1.0]heptane-2,3,4-triol, have been synthesized in 13 steps from 2,3,4,6-tetra-O-benzyl-D-galactose. The inhibitory activities of the two conformationally restricted amines, and their corresponding acetamides, were measured against commercial alpha-galactosidase enzymes from coffee bean and E. coli. The activity of the glycosyl hydrolase family GH27 enzyme (coffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 33 publications
0
27
0
1
Order By: Relevance
“…22 More recently, activated forms of these compounds have been used as covalent inhibitors. 23 In these cases the conformational restriction limits the accessible conformations to “off-pathway” 3 H 2 and 2 H 3 half-chairs 23 (or perhaps their related 1,4 boats) recently elegantly revealed by X-ray crystallography.…”
mentioning
confidence: 99%
“…22 More recently, activated forms of these compounds have been used as covalent inhibitors. 23 In these cases the conformational restriction limits the accessible conformations to “off-pathway” 3 H 2 and 2 H 3 half-chairs 23 (or perhaps their related 1,4 boats) recently elegantly revealed by X-ray crystallography.…”
mentioning
confidence: 99%
“…1b), compounds that could generate the desired carbocationic intermediate (Fig. 1c), improving on a previous route 28 to obtain the known alcohol 6 from commercially available 2,3,4,6-tetra-O-benzyl-D-galactopyranose (7) in 15.0% overall yield (Supplementary Methods and Supplementary Figs 1-5). We next achieved diastereoselective cyclopropanation of alkene 6 to obtain either 8 or 9 by including B2 equivalents of trifluoroacetic acid in the reaction mixture 29 and by judicious choice of the reaction solvent.…”
Section: Synthesis Of Glycosidase Inactivatorsmentioning
confidence: 99%
“…We also found that the rate of inactivation decreased in the presence of the competitive inhibitor 5 (ref. 28), indicating that inactivation is driven by action occurring at the enzymatic active site (Fig. 3b).…”
Section: Synthesis Of Glycosidase Inactivatorsmentioning
confidence: 99%
“…On the other hand, the spiroaziridines and spirodiaziridines 160 and 161 were prepared and evaluated as glycosidase inhibitors against -glucosidases from almonds, -glucosidase from Caldocellum saccharolyticum, andglucosidase from yeast with poor results compared with cyclopentylamine 162 (Figure 27) Two isomeric bicyclo[4.1.0]heptane 163 and 164 ( Figure 27) have been synthesized and evaluated against -galactosidase enzymes from coffee bean and E. coli [335]. The activity of the glycosyl hydrolase family GH27 enzyme (coffee bean) was competitively inhibited by the 1R,6S-amine with a value of 0.541 M. The E. coli -galactosidase exhibited a much weaker binding interaction with the 1R,6S-amine (IC 50 = 80 M).…”
Section: International Journal Of Carbohydrate Chemistrymentioning
confidence: 99%